PENINGKATAN RELIGIUSITAS MAHASISWA MELALUI PENDIDIKAN PESANTREN - Tri Wijayanti, fita (Penerbit CV Tentrem Karya Nusa, 2019)
Students are considered as agents of change who understood that the student is an intermediary or representative of society towards change. As an agent of change there must be a sense of responsibility to continue to forge themselves, learn a lot of things for the future of themselves and society. One that can be done by the students to learn a lot of things are learned in boarding school. Islamic Schools is one of the non-formal educational institutions and the oldest educational institutions in Indonesia. Islamic Schools is a traditional educational institution whose activity is to learn, understand, appreciate and practice the teachings of Islam with an emphasis on the importance of religious morals to guide everyday behavior. Being a student and also the students certainly not a light thing, to be able to divide their time between college and boarding school. However, pesantren indirectly much to contribute greatly to the students, such as: providing skills, informal leadership, service-oriented expertise, inventive (inventive), and can increase creativity. Key Words: student, education, boarding school